Nasosorption as a Minimally Invasive Sampling Procedure: Mucosal Viral Load and Inflammation in Primary RSV Bronchiolitis. (27th March 2017) - Thwaites, Ryan S.; Ito, Kazuhiro; Chingono, Jasmine M. S.; Coates, Matthew; Jarvis, Hannah C.; Tunstall, Tanushree; Anderson-Dring, Lauren; Cass, Lindsey; Rapeport, Garth; Openshaw, Peter J.; Nadel, Simon; Hansel, Trevor T.
Summary: We used nasosorption as a noninvasive method of respiratory mucosal sampling in a paediatric virology setting. Nasosorption was well tolerated and demonstrated respiratory syncytial virus load to be associated with disease severity and elevated mediators of inflammation. Abstract: Background: Existing respiratory mucosal sampling methods are flawed, particularly in a pediatric bronchiolitis setting. Methods: Twenty-four infants with bronchiolitis were recruited: 12 were respiratory syncytial virus (RSV)–positive, 12 were RSV-negative. Infants were sampled by nasosorption and nasopharyngeal aspiration (NPA). Results: Nasosorption was well tolerated and identified all RSV+ samples. RSV load measured by nasosorption (but not NPA) correlated with length of hospital stay ( P = .04) and requirement for mechanical ventilation ( P = .03). Nasosorption (but not NPA) levels of interferon γ, interleukin 1β, CCL5/RANTES, and interleukin 10 (IL-10) were elevated in RSV+ bronchiolitis (all P < .05), furthermore CCL5 and IL-10 correlated with RSV load ( P < .05). Conclusions: Nasosorption allowed measurement of RSV load and the mucosal inflammatory response in infants.